Disease Burden of Malignant Tumors Among Residents of Kunshan City, Jiangsu Province, 2006–2021 - Zhouquan FAN; Wenbin HU; Yixu JIN; Lyulin LU; Jie ZHOU; Lan TONG; Wei QIN (Zhongliu Fangzhi Yanjiu)
ObjectiveTo analyze the burden of disease of malignant tumors in Kunshan City from 2006 to 2021. MethodsThe global burden of disease research methodology was applied. The indicators of cancer incidence, mortality, and disability-adjusted life years (DALYs) in Kunshan were calculated using the data from the Tumor Registry System and Death Registry System in Kunshan. The changes in cancer were compared. ResultsIn 2021, the number of incidences and deaths and the DALYs of cancer were 4724 cases, 1618 cases, and 20887.90 person-years, respectively. The incidence, mortality, and DALYs rates were 427.42/100000, 146.39/100000, and 18.90‰. Compared with those in 2006, the incidence rate increased by 53.40%, and the mortality and DALYs rates decreased by 24.23% and 25.73%, respectively. The DALYs rate of cancer was higher for males than for females at 22.12‰ and 15.91‰ in 2021, respectively. The DALYs rate increased with age, and it started to increase sharply after 45 years of age. The top 10 cancers in 2021 in terms of DALYs were lung cancer, stomach cancer, colorectal cancer, liver cancer, pancreatic cancer, breast cancer, leukemia, esophageal cancer, brain and nervous system cancer, and gallbladder and biliary tract cancer, accounting for 83.83% of all cancers. The proportion of years lived with disability (YLD) in DALYs increased continuously (27% in 2021), with females increasing faster than males. ConclusionThe disease burden of cancer in Kunshan City remains high, and the incidence of cancer must be reduced by developing comprehensive measures and continuously strengthening the capacity of early screening and treatment of cancer.